ANALISIS IMPLEMENTASI PEMBERDAYAAN MASYARAKAT DALAM STRATEGI PROMOSI KESEHATAN DAN PENGARUHNYA TERHADAP PARTISIPASI MASYARAKAT DALAM PENCEGAHAN GIZI BURUK PADA BALITA DI KECAMATAN HELVETIA MEDAN - Zuhrina Aidha,S.Kep., M.Kes (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT               Malnutrition and severe malnutrition among children under five is one of the health problems currently receive enough attention. An estimated 15% of children under five in the world were underweight. Various strategies have been developed to prevent and handle this nutritional problem by comprehensive approach, which prioritizes health promotion and by teartment and recovery.              The purpose of the study was to analyze the implementation of health promotion strategies and its effect on community participation in the prevention of malnutrition in children under five in the area of the Helvetia health center Medan in 2014. This research used a mixed methods approach is combined with qualitative in-depth interviews to the 5 informants, and quantitative approach by interviewing 95 respondents.               The result of the research show that the implementation of advocacy activities is good enough with the commitment of the chief areas for prevention and handle of malnutrition, but based on the survey 76.8% of the public opinion on community empowerment activities are in the category of no good and there is a relationship between community empowerment with community participation in the prevention of malnutrition in children under five. Empowerment variables are variables that most influence on community participation (odds ratio value of 4.439).               It is recommended that the local government increase the activity of advocacy so that political support, especially policy support in the farm or Government Regulation, can be obtained. It is also recommended that favorable atmosphere development for people through media should be activated and established community empowerment should be improved.  Keywords:  Implementation, Health Promotion Strategy, Community Empowerment, Community Participation, Severe Malnutrition